The farewell [videorecording (DVD)] - Wang, Lulu (Director); Wang, Lulu (Director); Awkwafina, 1989-; Ma, Tzi; Lin, Diana (Lionsgate, 2019)
When a Chinese family finds out that their grandmother has only a short time left to live, they plan a family reunion before she dies without telling her.